2017
DOI: 10.3354/meps11970
|View full text |Cite
|
Sign up to set email alerts
|

Invasive red king crabs feed on both spawned-out capelin and their eggs

Abstract: The aim of the present study was to test the hypothesis that the invasive red king crab Paralithodes camtschaticus may hamper capelin (Mallotus villosus) recruitment through egg consumption. Field studies (2005, 2006), laboratory experiments (2011), and models of consumption were applied. To explore the response of the predator to prey density, crab abundance and capelin egg density were estimated in stratified study areas. Stomach evacuation rates of capelin eggs in red king crab stomachs were investigated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…trypanosome blood parasites by hosting the leech Johanssonia arctica: Hemmingsen et al, 2005Hemmingsen et al, , 2010;  designated as an aquatic nuisance species in the USA by the Aquatic Nuisance Species Task Force (ANSTF) since 1998;  in 2002 the ANSTF implemented a Green Crab Management Plan to assess the impacts and prevent, eradicate, and control the species;  negative impacts have been demonstrated on a number of benthic invertebrate taxa, including bivalves and other crustaceans (Floyd and Williams, 2004;Grosholz et al, 2000;Pickering and Quijón, 2011;Gehrels et al, 2016);  indirect negative effects have been suggested on physical characteristics of benthic habitats through bioturbation (Schratzberger and M. Warwick, 1999;Neira et al, 2006;Malyshev and Quijón, 2011;Lutz-Collins et al, 2016);  no parasite-related indirect effects have been emphasized to date; however, it has been suggested that the species may have a lower susceptibility to pathogens than other decapod crustaceans (e.g. Hematodinium infections: Hamilton et al, 2010); Economic Impact  negative effects have been indicated on the recruitment of valuable finfish species by feeding on egg-clutches (Mikkelsen and Pedersen, 2012; but see Dvoretsky, 2015 andPedersen, 2017);  non-univocal effects have been highlighted on the abundance of finfish and crustacean species of economic interest (Falk-Petersen et al, 2011;Jørgensen and Spiridonov, 2013;Dvoretsky and Dvoretsky, 2015);  negative impacts have been indicated on juvenile stages of fish and crustacean species of economic interest (Taylor, 2005;Rossong et al, 2006);  considerable economic impacts have been long acknowledged on native shellfish products; for example, in 2005 the Oregon Dungeness Crab Commission estimated the potential impact on the west coast dungeness crab (Metacarcinus magister Dana, 1852) fishery in $50 million, while Lovell et al (2007) showed that the estimated average annual losses to east coast  severe interference of bycatch with traditional fishing methods, as crabs feed on captured commercial species, and damage fishing gears; bycatch impels the abandon of historically important coastal fishing grounds (Godøy et al, 2003;Furevik et al, 2008;…”
Section: Distribution Abundance and Connectivity Of Populationsmentioning
confidence: 99%
“…trypanosome blood parasites by hosting the leech Johanssonia arctica: Hemmingsen et al, 2005Hemmingsen et al, , 2010;  designated as an aquatic nuisance species in the USA by the Aquatic Nuisance Species Task Force (ANSTF) since 1998;  in 2002 the ANSTF implemented a Green Crab Management Plan to assess the impacts and prevent, eradicate, and control the species;  negative impacts have been demonstrated on a number of benthic invertebrate taxa, including bivalves and other crustaceans (Floyd and Williams, 2004;Grosholz et al, 2000;Pickering and Quijón, 2011;Gehrels et al, 2016);  indirect negative effects have been suggested on physical characteristics of benthic habitats through bioturbation (Schratzberger and M. Warwick, 1999;Neira et al, 2006;Malyshev and Quijón, 2011;Lutz-Collins et al, 2016);  no parasite-related indirect effects have been emphasized to date; however, it has been suggested that the species may have a lower susceptibility to pathogens than other decapod crustaceans (e.g. Hematodinium infections: Hamilton et al, 2010); Economic Impact  negative effects have been indicated on the recruitment of valuable finfish species by feeding on egg-clutches (Mikkelsen and Pedersen, 2012; but see Dvoretsky, 2015 andPedersen, 2017);  non-univocal effects have been highlighted on the abundance of finfish and crustacean species of economic interest (Falk-Petersen et al, 2011;Jørgensen and Spiridonov, 2013;Dvoretsky and Dvoretsky, 2015);  negative impacts have been indicated on juvenile stages of fish and crustacean species of economic interest (Taylor, 2005;Rossong et al, 2006);  considerable economic impacts have been long acknowledged on native shellfish products; for example, in 2005 the Oregon Dungeness Crab Commission estimated the potential impact on the west coast dungeness crab (Metacarcinus magister Dana, 1852) fishery in $50 million, while Lovell et al (2007) showed that the estimated average annual losses to east coast  severe interference of bycatch with traditional fishing methods, as crabs feed on captured commercial species, and damage fishing gears; bycatch impels the abandon of historically important coastal fishing grounds (Godøy et al, 2003;Furevik et al, 2008;…”
Section: Distribution Abundance and Connectivity Of Populationsmentioning
confidence: 99%